2023
DOI: 10.7150/thno.82552
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal STIMATE derived from type II alveolar epithelial cells controls metabolic reprogramming of tissue-resident alveolar macrophages

Abstract: Background: Complete abolition of alveolar epithelial cells (AECs) is characteristic of end-stage lung disease. Transplantation therapy of type II AECs (AEC-IIs) or AEC-IIs-derived exosomes (ADEs) have been proposed as a means of repairing injury and preventing fibrosis. However, the mechanism by which ADEs balances airway immunity and alleviates damage and fibrosis remains unknown. Methods: We investigated STIM-activating enhancer-positive ADEs (STIMATE + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…However, cross-talk between airway epithelial cells and alveolar macrophages mediated by exosomal miRNAs in ARDS has rarely been reported. A recent study indicated that exosomal STIMATE, derived from type II alveolar epithelial cells, regulates the subpopulation proportion and metabolic reprogramming of macrophages in patients with ARDS and pulmonary brosis [20]. In our study, miR-301a-3p, screened using GeneChip from the GSE database, served as a potential regulator of macrophage polarization and immune responses in ARDS.…”
Section: Discussionmentioning
confidence: 81%
“…However, cross-talk between airway epithelial cells and alveolar macrophages mediated by exosomal miRNAs in ARDS has rarely been reported. A recent study indicated that exosomal STIMATE, derived from type II alveolar epithelial cells, regulates the subpopulation proportion and metabolic reprogramming of macrophages in patients with ARDS and pulmonary brosis [20]. In our study, miR-301a-3p, screened using GeneChip from the GSE database, served as a potential regulator of macrophage polarization and immune responses in ARDS.…”
Section: Discussionmentioning
confidence: 81%
“…We have successfully associated specific experimental findings with clinical relevance, as a correlation was discovered between the components responsible for the anti-inflammatory effect of M2φ-EVs and the disease severity in ARDS patients (Figure 10). In recent years, the pivotal role of alveolar macrophage polarisation in controlling inflammatory lung diseases has gained recognition (Feng et al, 2023;Song et al, 2019). Therefore, numerous studies have focused on modulating the polarisation of macrophages, particularly with the goal of increasing the proportion of M2-like alveolar macrophages to manage ALI/ARDS (Feng et al, 2023;Song et al, 2019).…”
Section:  Discussionmentioning
confidence: 99%
“…M1φ are primarily involved in proinflammatory processes, and are a major source of numerous cytokines including IL‐6, TNF‐α and IL‐1β, which contribute to tissue damage following infections (Wang et al., 2020 ). In contrast, M2φ have been shown to play anti‐inflammatory and tissue repair roles in mouse models of acute liver failure, acute kidney injury, colitis and ALI (Bai et al., 2021 ; Feng et al., 2023 ; Lin et al., 2014 ; Song et al., 2019 ; Tang et al., 2020 ), partly by inhibiting NLRP3 inflammasome activation (Bai et al., 2017 ; Bai et al., 2018 ; Bai et al., 2019 ). However, practical applications of macrophage‐oriented cell therapy in vivo face several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes derived from STIM-activating enhancer-positive type II alveolar epithelial cells (AEC II) regulate high Ca2+ responsiveness and long-term Ca2+ signaling, thereby maintaining an M2-like immune phenotype and metabolic selection. This modulation helps attenuate early acute injury and helps prevent late-stage fibrosis ( Feng et al, 2023 ). Additionally, macrophages can be classified based on Ly6C into Ly6Clow, Ly6Chi, and Ly6C- macrophages.…”
Section: Exosomes Target In Macrophage-mediated Repair Of the Pulmona...mentioning
confidence: 99%